2008
DOI: 10.1002/jsfa.3262
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion cooking of barley flour and process parameter optimization by using response surface methodology

Abstract: BACKGROUND: The nutritional profile of barley places it in a prime position for development of a new extruded-expanded snack food with health benefits. It was therefore the aim to investigate the effect of extrusion processing variables on system parameters (specific mechanical energy, die pressure and die melt temperature) and physical properties (expansion, bulk density, texture and color) of barley flour extrudates and to optimize processing conditions for production of extruded snack food from barley flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 35 publications
4
63
0
2
Order By: Relevance
“…The increase in FMC caused decrease in expansion which may occur due to reduction of elasticity of dough through plasticization of melt (Ding et al 2005, Ding et al 2006. Altan et al (2008b) also reported significant effect of barrel temperature on SEI of barley flour extrudates. According to Chinnaswamy and Hanna (1988), expansion of corn starch extrudates increased as the barrel temperature increased from 110 to 140°C and declined with further increase in temperature.…”
Section: Resultsmentioning
confidence: 82%
“…The increase in FMC caused decrease in expansion which may occur due to reduction of elasticity of dough through plasticization of melt (Ding et al 2005, Ding et al 2006. Altan et al (2008b) also reported significant effect of barrel temperature on SEI of barley flour extrudates. According to Chinnaswamy and Hanna (1988), expansion of corn starch extrudates increased as the barrel temperature increased from 110 to 140°C and declined with further increase in temperature.…”
Section: Resultsmentioning
confidence: 82%
“…2d). Altan et al (2008) investigated the physical characteristics of barley flour extrudates and reported that temperature had a dominant effect on the bulk density and in respect of screw speed they found a minor effect. The positive relationship between temperature and bulk density could be explained by the decrease of expansion with increase of temperature.…”
Section: Product's Bulk Densitymentioning
confidence: 99%
“…Altan et al (2008) investigated the physical characteristics of barley flour extrudates and reported that temperature had a dominant effect on the BD and in respect of screw speed they found a minor effect. Altan et al (2008) investigated the physical characteristics of barley flour extrudates and reported that temperature had a dominant effect on the BD and in respect of screw speed they found a minor effect.…”
Section: Product's Bdmentioning
confidence: 99%